Artificial Intelegence Perbandingan Algoritma Simple Hill Climbing Dan Steepest Ascent Hill Climbing Dalam Media Pembelajaran Alfabert - Sari, Mike Febri Mayang; Sari, Dian Permata (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
This game is of interest to children aged 4 to 6 years and is very useful and able to sharpen the brain, improve memory for children. The Alphabert Game Algorithm must have a clear process of stages in order to achieve a goal in the Search system. Alphabert's Game Logic uses the Simple Hill Climbing Algorithm and the Ascent Hill Climbing Algorithm which is often used in artificial intelligence. The problem that occurs in the research, is the lack of user understanding to find a suitable algorithm to arrange the Alfabert game according to the principle of how an algorithm works. The Alphabert compilation game must follow predetermined rules in order to obtain the correct algorithm so as to produce an arrangement that is in accordance with the initial data. The work process of completing the preparation of the alphabet. The benefits of this research provide a solution to solve the Alfabert game in accordance with the rules of the Imple Hill Climbing algorithm, the Ascent Hill Climbing Search Algorithm so as to produce a solution in the search method. To solve this case there are 3 things that must be considered1. If the new state is the goal then exit 2. If not the goal, but the value is better than the current state, then make the new state into the current state 3. If the new state is not better than the current state, then continue the next iteration. Based on the search process, the final result of Alfabert's game is in the correct position of 8 squares according to the initial rule, then the search is stopped and produces a goal.